Homosexual adolescents: problems and coping in the coming out process - Oliveros, Consuelo G. (Animo Repository, 1999)
This study identifies the influential factors in the coming out process, problems, and coping of the homosexual adolescents in the different stages of identity formation. Descriptive analysis method was employed and a combination of purposive and snowball/chain referral technique was used in obtaining the 30 gay and lesbian adolescent respondent. A self-constructed interview guide based on the identity formation model proposed by Cass (1979) was utilized in conducting one-on-one in-depth interview with the respondents. Data gathered were content analyzed based on the theoretical framework of this study. Major findings indicated that social factors (e.g. friends' acceptance and support) influenced most of the gay and lesbian adolescents' decision to come out. It was also found that not all respondents had undergone the six stages of identity formation. Some (5) did not pass the stage of identity confusion, while one got stuck in it. Others (4) did not reach the stages of identity pride and synthesis. The gay and lesbian adolescents encountered various problems in the different stages of the coming out process. However, they were able to cope with these concerns effectively through direct confrontation and defense mechanisms such as rationalization, displacement, and sometimes avoidance of conflicting situations. Remarkable differences between gays and lesbians were observed in relation to disclosing their identity as well as in their future plans. Most gays were still in the pit of dilemma revealing themselves to their parents, unlike lesbians who already had disclosed themselves to all the people they knew. Moreover, for the lesbians, to prove their worth, finishing their studies and finding a job were important whereas for gays, aside from attaining education and finding a career, establishing a family with their partner is a priority. Gays and lesbians had reached the stage of identity synthesis.